2023
DOI: 10.1186/s40478-022-01489-3
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the glutamatergic photoreceptor synapse in the P301S mouse model of tauopathy

Abstract: Tauopathies, including Alzheimer’s disease, are characterized by retinal ganglion cell loss associated with amyloid and phosphorylated tau deposits. We investigated the functional impact of these histopathological alterations in the murine P301S model of tauopathy. Visual impairments were demonstrated by a decrease in visual acuity already detectable at 6 months, the onset of disease. Visual signals to the cortex and retina were delayed at 6 and 9 months, respectively. Surprisingly, the retinal output signal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Taken together, these results show for the first time that the cleavage at the N-terminal tau with the release of diagnostic 20–22 kDa toxic neuropeptide (i.e.,NH 2 htau) is not only restricted to the retina and associated ocular structures of 6-month-old Tg2576 AD mice [ 12 ], but is also extended to their primary visual cortex (V1 area), in agreement with studies reporting that the accumulation of other pathogenic misfolded and/or hyperphosphorylated tau species is detectable along the entire visual system both in different preclinical AD animal models and AD subjects [ 7 , 79 , 80 , 81 , 82 , 83 ]. More importantly, the NH 2 htau fragment is successfully immunodepleted in the V1 area by 12A12mAb administration, which also exerts an anti-amyloidogenic effect by reducing the local expression levels of APP/Aβ ( Supplementary Figure S1 ), just as we reported to occur in the hippocampus and in the retina of this transgenic strain [ 12 , 42 ].…”
Section: Resultssupporting
confidence: 77%
“…Taken together, these results show for the first time that the cleavage at the N-terminal tau with the release of diagnostic 20–22 kDa toxic neuropeptide (i.e.,NH 2 htau) is not only restricted to the retina and associated ocular structures of 6-month-old Tg2576 AD mice [ 12 ], but is also extended to their primary visual cortex (V1 area), in agreement with studies reporting that the accumulation of other pathogenic misfolded and/or hyperphosphorylated tau species is detectable along the entire visual system both in different preclinical AD animal models and AD subjects [ 7 , 79 , 80 , 81 , 82 , 83 ]. More importantly, the NH 2 htau fragment is successfully immunodepleted in the V1 area by 12A12mAb administration, which also exerts an anti-amyloidogenic effect by reducing the local expression levels of APP/Aβ ( Supplementary Figure S1 ), just as we reported to occur in the hippocampus and in the retina of this transgenic strain [ 12 , 42 ].…”
Section: Resultssupporting
confidence: 77%
“…After reading Hart de Ruyter et al [ 5 ], we decided to quantify thickness changes of the IPL, OPL, and INL in tauopathies compared with healthy controls (HCs) and non-tau-related pathologies in 4RTNI. We also quantified changes in the outer nuclear layer (ONL)—which contains the cell bodies of rod and cone photoreceptors—in line with a recent publication by Arouche-Delaperche that described functional impairment directly due to tau deposition and indirectly due to tau-associated microglial activation in animal models of tauopathy [ 2 ]. We further investigated changes in the peripapillary retinal nerve fiber layer (pRNFL) and the ganglion cell layer (GCL), which contain the axons and cell bodies of retinal ganglion cells, respectively, and are of interest as markers of neurodegeneration [ 4 ].…”
mentioning
confidence: 99%
“…Ganglion cell loss was not investigated by Hart de Ruyter et al [ 5 ], but was shown recently by Arouche-Delaperche in a tauopathy animal model [ 2 ]. The absence of GCL thinning in our subset analysis of patients ≤ 5 years since onset suggests that ganglion cell loss and therefore retinal neurodegeneration occur later in the disease.…”
mentioning
confidence: 99%